Time to Change the Objectives Hemodynamic to Guide the Perioperative Fluid Management? - M Pilar Rodrigo Casanova (Global Journal of Perioperative Medicine - Peertechz Publications, 2017)
Short Communication Major surgery is a considerable physiologic insult that can be associated with significant morbidity and mortality. The prevention of perioperative morbidity is a determining factor in providing high-quality in health care, since the occurrence of postoperative complications adversely affects postoperative survival and increase healthcare costs [1]. The fluids are intravenous drugs most commonly used by anesthesiologist during the perioperative period. Incorrect used contributes greatly to the increased morbidity, thus fluid management influences significantly in patients outcomes. The perioperative fluid therapy and hemodynamic management, is one of the cornerstones of the medical care of surgical patients. However, and unlike other therapeutics practices, there is no uniformity in dosage and timing of administering intravenous fluid.There is considerable variability in fluid administration among specialist, the volume of fluid administered depends to a large extent on the individual practitioner, and the most use clinical end points such as urine output, mean arterial blood pressure, or central venous pressure that have little to do with the hemodynamic goals of fluid administration, at this time.